1991
DOI: 10.1111/j.1365-2907.1991.tb00289.x
|View full text |Cite
|
Sign up to set email alerts
|

The past history and recent decline of Badgers Meles tneles in Essex: an analysis of some of the contributory factors

Abstract: The past history of the Badger in Essex is reviewed. It is shown that the population has fluctuated in the past, and that heavy gamekeeping pressure probably reduced numbers at the turn of the century, although Badgers were probably never as rare as early recorders believed. In recent years Badgers have been rare or absent in many areas of the county because they did not afford suitable sett sites, and the county as a whole is not particularly good for Badgers. Against this already low‐density Badger populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
3

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 14 publications
1
6
0
3
Order By: Relevance
“…We found that badgers avoided areas around villages, industries or habitats with human settlements. These findings are consistent with evidence from other countries where urban and infrastructure expansion contributed to the decline of badger populations (Lankester et al, 1991;Skinner et al, 1991). Although no studies have been carried out on the impact of urban expansion on badger populations in our study area, the increase in urban sprawl and associated infrastructures in the last few decades in Spain (OSE, 2006) is believed to have increased habitat loss, population fragmentation and traffic causalities, primarily affecting low density badger populations (Virgós and Casanovas, 1999a;Revilla et al, 2000).…”
Section: Discussionsupporting
confidence: 93%
“…We found that badgers avoided areas around villages, industries or habitats with human settlements. These findings are consistent with evidence from other countries where urban and infrastructure expansion contributed to the decline of badger populations (Lankester et al, 1991;Skinner et al, 1991). Although no studies have been carried out on the impact of urban expansion on badger populations in our study area, the increase in urban sprawl and associated infrastructures in the last few decades in Spain (OSE, 2006) is believed to have increased habitat loss, population fragmentation and traffic causalities, primarily affecting low density badger populations (Virgós and Casanovas, 1999a;Revilla et al, 2000).…”
Section: Discussionsupporting
confidence: 93%
“…In general, the setts used by the Don Ä ana badgers were small, with only eight recorded setts having ®ve or more entrances; the largest sett found had fewer entrances than the average main sett in England (Cresswell et al, 1990). This small size also occurs in other medium and low density populations, as in Norway (Broseth et al, 1997), Essex county in England (Skinner, Skinner & Harris, 1991b), the Alpine zone of the Bavarian Alps (Bock, 1986) and Scotland (Kruuk, 1989). None of the setts found in our study area was used all year round with only 30% of radiolocations on average coming from the most-used sett in each territory (Revilla, 1998).…”
Section: Discussionmentioning
confidence: 95%
“…The Protection of Badgers Act (1992) has also been cited as a potential reason for the recovery in badger numbers nationally. Pain (1997) suggests that`The recovery is almost wholly as a result of the reduction in snaring, shooting and digging for badgers', factors known to have suppressed badger numbers in the past (Skinner, Jefferies & Harris, 1989;Skinner, Skinner & Harris, 1991).…”
Section: Discussionmentioning
confidence: 99%